A Follow-Up Study of the Effects of An Arm Support Exoskeleton on Physical Demands and Task Performance During Simulated Overhead Work. Issue 3 (2nd October 2019) - Kim, Sunwook; Nussbaum, Maury A.
OCCUPATIONAL APPLICATIONS: This study supports that use of an arm-support exoskeleton (ASE) can lower the activity of shoulder and lower trunk muscles during an overhead drilling and a light assembly task, and also improve work quality in terms of the number of errors made during drilling. Integrating the findings from earlier studies, though, the current results suggest that such benefits of ASE use likely depend on the specific ASE and work tasks in which it is used. Further, a decrease in the number of drilling errors with the fixed drilling pace used here can be explained by a speed-accuracy tradeoff. In practice, this tradeoff has implied that when an ASE is provided, workers may need a reasonable training/acclimation period with an ASE, to develop a mental model and an optimal work strategy to adopt to their ASE-enhanced physical capacity without any adverse consequences. TECHNICAL ABSTRACT Background : Overexertion and bodily reaction remain leading causes of work-related musculoskeletal disorders. Occupational use of an exoskeleton has been recognized recently as an alternative intervention approach to reduce physical demands and fatigue experienced in a range of occupational tasks. Purpose: This study replicated many aspects of an earlier study of using an arm-support exoskeleton (ASE) during simulated overhead drilling and light assembly (Kim et al., 2018 ), and was complete to reexamine the beneficial effects of ASE and determine if a speed-accuracy tradeoff might explain the increase in the number of errors reported in the noted earlier study. Methods: In a controlled lab-based experiment, 12 gender-balanced participants performed a simulated overhead repetitive drilling (at 1 hole per 10 s) and a light assembly task at two different work heights, both with and without a commercial ASE. Activity of shoulder and lower trunk muscles, perceived discomfort, and drilling performance were measured. Results: Using the ASE reduced peak and median normalized muscle activity levels, respectively, by up to 52.5% and 60.6% for the shoulder, and ∼29% and ∼16% for the lower trunk. Reductions in shoulder muscle activity and perceived discomfort were often more substantial at the overhead work height. Using the ASE also led to fewer drilling errors (up to ∼92% reduction), especially with a heavier tool and/or at the overhead work height. Conclusions: This study supplements earlier evidence that supports the efficacy of ASE use in reducing physical demands of the upper extremity and the lower back during overhead work. However, the latter "secondary" benefit, beyond the specific ASE design focus, is likely conditional on the specific ASE design and the specific work task in which it is used. Effects of an ASE on drilling task performance were also task-specific, dependent on how task pacing is controlled and consistent with a traditional speed-accuracy tradeoff.